The role of oxygen regulation and algal growth parameters in hydrogen production via biophotolysis. Issue 1 (February 2022) - Javed, Muhammad Asad; Zafar, Abdul Mannan; Aly Hassan, Ashraf; Zaidi, Asad A.; Farooq, Muhammad; El Badawy, Amro; Lundquist, Tryg; Mohamed, Mohamad Mostafa Ahmed; Al-Zuhair, Sulaiman
Abstract: One of the biggest challenges for hydrogen (H2 ) production via biophotolysis is the sensitivity of the process to oxygen (O2 ), which is the primary inhibitor of the hydrogenase enzyme responsible for H2 production. The present study reviews the literature on methods to enhance H2 production by creating suitable conditions to enable the activity of the hydrogenase enzyme. Techniques studied include the regulation of available O2 and utilizations of antioxidants. Furthermore, optimizing algal growth parameters such as pH, temperature, light intensity, and cell density can keep the algal cells alive for a more extended period for biophotolysis and can directly or indirectly activate enzymatic activity for enhanced H2 production. Various O2 regulating techniques, i.e., mineral deprivation, oxygen-reducing agents/scavengers, co-culturing of microalgae with bacteria, the addition of antioxidants and nanoparticles have been analyzed and discussed in this review. Analysis of strengths, weaknesses, opportunities, and threats/challenges (SWOT) also presents the limitations and advantages of H2 production via biophotolysis. This review insights that employing all the favorable techniques with suitable operating parameters simultaneously can result in enhanced H2 yield and better process sustainability. However, O2 regulating techniques such as co-culturing with bacteria and the use of antioxidants/nanoparticles appear to be the most significant in H2 production via biophotolysis towards environmental sustainability and green energy. Graphical Abstract: ga1 Highlights: H2 production through biophotolysis using microalgae is the cleanest energy source. Oxygen scavenging is a vital parameter in H2 production enhancement. Optimization of process parameters keeps oxygen and H2 concentrations inverse. Various techniques, including nanoparticles, are effective in controlling process inhibitors. Use of antioxidants and O2 reducing substrates effectively enhances H2 production.